Synthesis, Conformational Analysis and Antinociceptive Activity of 1-[N-Methyl-(2-phenylethyl)amino]methyl-1,2,3,4-tetrahydroisoquinoline Derivatives - Tabatabaia, Sayyed Abbas; Zarrindast, Mohammad Reza; Lashkari, Saoka Barghi; Shafiee, Abbas (Arzneimittelforschung, 1999)
New derivatives of 1-[N-methyl-(2-phenylethyl)amino]methyl-1,2,3,4-tetrahydroisoquinoline were synthesized. The antinociceptive activity of the compounds, determined by the mouse tail-flick test, showed that the introduction of a hydroxy substituent in position 5 of the isoquinoline nucleus generated compounds 4c and 5c, which were as potent as codeine. Conformational analysis and superimposition of energy minima conformers of the compounds on phenazocine revealed that the main proposed opioid pharmacophores were well matched.
Keywords: 1,2,3,4-Tetrahydroisoquinoline derivatives, antinociceptive activity; conformational analysis, synthesis